PENGEMBANGAN INSTRUMEN FOUR - TIER DIAGNOSTIC TEST UNTUK MENGIDENTIFIKASI MISKONSEPSI PADA MATERI DINAMIKA LITOSFER DI SMA KABUPATEN CIANJUR - Setianisa, Talita Rizki; Ruhimat, Mamat; Waluya, Bagja (Faculty of Educational Sciences, UIN (State Islamic University) Syarif Hidayatullah Jakarta, 2025)
Misconceptions refer to understandings that do not align with scientifically accurate concepts. Identifying misconceptions is essential for enhancing learning effectiveness. This study aims to develop a Four-tier Diagnostic Test instrument to identify students' misconceptions regarding lithosphere dynamics in senior high schools in Cianjur Regency. The research employs the 4D development model with the Rasch Model, consisting of four stages: define, design, develop, and disseminate. However, this study is limited to the identification stage. The sampling technique used random sampling, with a total sample of 440 students from five senior high schools. The Four-tier Diagnostic Test instrument was validated using the Rasch Model, with Outfit MNSQ values ranging from 0.66 to 1.37 and Outfit ZSTD values from -2.90 to 2.90. The instrument’s reliability, measured by Cronbach’s Alpha, was 0.74. The level of students’ misconceptions varied, with School P having the highest misconception rate at 32.4%, while School N had the lowest at 17.1%. Among subtopics, exogenous forces had the highest misconception rate at 29%, whereas tectonic processes had the lowest at 6.3%. In conclusion, the Four-tier Diagnostic Test is an effective instrument for identifying students' misconceptions regarding lithosphere dynamics.